Extracurricular activities and childhood obesity: An epidemiological study among 10–12 years old children. (January 2021) - Notara, Venetia; Kanellopoulou, Aikaterini; Diamantis, Dimitrios V.; Antonogeorgos, George; Magriplis, Emmanuella; Paola Rojas-Gil, Andrea; Kornilaki, Ekaterina N.; I. Kosti, Rena; Lagiou, Areti; Panagiotakos, Demosthenes B.
Highlights: Engagement in out-of-school sport activities means less likelihood of obesity. Important role of extracurricular activities on children's weight status. Out-of-school reading was associated with increased likelihood of obesity. Abstract: Childhood obesity rates have shown a rising trend in the past years, becoming a public health challenge and threat. The aim of this study was to examine the association between extracurricular activities and weight status, among children. A survey was performed in 1728 primary school Greek students, during school years 2014–2016. Dietary and lifestyle habits, such as engagement in a variety of extracurricular activities were evaluated. The KIDMED Score was used to assess the level of adherence to the Mediterranean diet. Children's Body Mass Index (BMI) was calculated and classified as normal, overweight, or obese, according to the International Obesity Task Force (IOTF) classification. The prevalence of overweight was 21.7% and obesity 5.0%, with a greater proportion of overweight/obese boys than girls (32.4% vs. 23.3%; p  < 0.001). Increased engagement on extracurricular activities, such as watching TV, reading out-of-school material and reduced participation in sports activities were associated with a higher likelihood of overweight/obesity ( p  < 0.05). Extracurricular physical activities can be promoted within the family environment and incentives or obstacles should be considered and addressed.